2021
DOI: 10.1186/s13045-021-01063-9
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic strategies in RET gene rearranged non-small cell lung cancer

Abstract: The recent approvals by the Food and Drug Administration several tumor-agnostic drugs have resulted in a paradigm shift in cancer treatment from an organ/histology-specific strategy to biomarker-guided approaches. RET gene fusions are oncogenic drivers in multiple tumor types and are known to occur in 1–2% of non-squamous NSCLC patients. RET gene fusions give rise to chimeric, cytosolic proteins with constitutively active RET kinase domain. Standard therapeutic regimens provide limited benefit for NSCLC patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 41 publications
0
54
0
2
Order By: Relevance
“…Recent Cancer Cytopathology December 2021 clinical trials in patients with various RET fusion-positive cancers using RET inhibitors, including selpercatinib and pralsetinib, have demonstrated therapeutic responses with rates ranging from 56% to 63%. [26][27][28] Currently, rationales for molecular analysis in selected salivary neoplasias detected by FNA are useful when one is considering preoperative neoadjuvant therapy, in cases in which surgical planning would be either altered or deferred on the basis of the result, or in cases in which surgery is not an option because of the patient's clinical status. Recent studies with kinase fusion-related thyroid carcinomas 29,30 provide a useful template to apply in the context of cytologic and small biopsy specimens of kinase-fusion or kinase-mutated salivary gland malignancies such as IDC when the result would potentially affect the clinical management (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent Cancer Cytopathology December 2021 clinical trials in patients with various RET fusion-positive cancers using RET inhibitors, including selpercatinib and pralsetinib, have demonstrated therapeutic responses with rates ranging from 56% to 63%. [26][27][28] Currently, rationales for molecular analysis in selected salivary neoplasias detected by FNA are useful when one is considering preoperative neoadjuvant therapy, in cases in which surgical planning would be either altered or deferred on the basis of the result, or in cases in which surgery is not an option because of the patient's clinical status. Recent studies with kinase fusion-related thyroid carcinomas 29,30 provide a useful template to apply in the context of cytologic and small biopsy specimens of kinase-fusion or kinase-mutated salivary gland malignancies such as IDC when the result would potentially affect the clinical management (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, both RET and PDGFRB are clinically relevant LUAD cancer genes. RET has protooncogene properties and its fusions, which occur in 1-2% of LUAD 64 , are associated with a high risk of brain metastasis 65 . However, last clinical trials indicated that they may be effectively targeted by RET tyrosine kinase inhibitors as pralsetinib, selpercatinib 64 .…”
Section: Discussionmentioning
confidence: 99%
“…RET has protooncogene properties and its fusions, which occur in 1-2% of LUAD 64 , are associated with a high risk of brain metastasis 65 . However, last clinical trials indicated that they may be effectively targeted by RET tyrosine kinase inhibitors as pralsetinib, selpercatinib 64 . PDGFRB is a member of the PDGF/PDGFR axis that is recognized as a key regulator of mesenchymal cell activity in TME 66 , and several new agents (linifanib, motesanib, olaratumab) that block the PDGFR signaling are being tested in LUAD 67 .…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent partners occur in KIF5B and CCD6, which represent around 60% and 20% of cases, respectively [137]. Different therapeutic medications targeting RET fusions have been developed, and, to date, selpercatinib and pralsetinib medications are proposed while waiting for marketing approval by the FDA and EMA [140][141][142][143][144][145]. However, testing for these fusions will now become systematic at diagnosis for all patients presenting with advanced-stage NS-NSCLC, knowing that patients with RET fusions do not generally respond well to immune checkpoint inhibitors (ICIs) [146][147][148][149].…”
Section: Biomarkers Just Beyond the "Big Five" In 2021 221 Ret Fusionsmentioning
confidence: 99%